Awareness of the principles of green chemistry among middle school teachers (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to recognize awareness of the principles of green chemistry among chemistry teachers and to recognize the significance of differences in awareness of the principles of green chemistry according to the sex variable and the research identified the chemistry teachers in the preparatory schools of the Directorate of Diwaniyah Education, for the academic year 2020-2021 and the sample size (130) teachers and schools randomly selected. To achieve the objectives, The results showed that chemistry teachers do not have awareness of the principles of green chemistry and the absence of differences for the sex variable, and the researchers recommended in the light of the results many recommendations and proposals.